LEGILE PERFECŢIONĂRII ÎNTRE BIBLIOTECĂ-FORMATOR-BIBLIOTECAR. INCURSIUNE TEORETICĂ CU EXCURS PRAXIOLOGIC - KULIKOVSKI, Conferențiar universitar , Lidia (BIBLIOPOLIS, 2020)
Socrates said that we are what we repeatedly do. Librarians as a profession, are people of knowledge, so people able to improve themselves continuously. But also about librarians (about critical mass range) is said they can not to update their knowledge, they are not interested in training, do not make eff ort to their professional development. This bias, is a part of mentality of our founders, partners and our users, the mentality of other professions, including some librarians. Largely the librarians fueling this situation because the perfection starts from the mentality. Can trainers, libraries infl uence, change anything? Can!